Potensi dan Pengembangan Daya Tarik Kawasan Wisata di Daerah Rawan Bencana Gunung Agung, Kabupaten Karangasem, Bali - Tjok Istri Priti Mahendradevi; I Nyoman Darma Putra; I Nyoman Sunarta (JURNAL MASTER PARIWISATA, 2022)
Volcano eruption becomes one of the most dangerous disasters as it can’t be predicted and is potential to be catastrophic. One of the most vulnerable industries impacted by volcano eruption is tourism industry. However, volcano has many tourism potencies. Mount Agung in Karangasem regency is an active volcano which has various tourism potencies. However, most of the tourism potencies are located in eruption prone-areas. This research examines develop and undevelop tourism potencies at Mount Agung tourism area, development problems, and the development strategies. This research uses qualitative approach and the data collected by literature study, observation, and in-depth interviews. The data is analyzed with ecotourism theory, tourist object components theory, and tourist object development strategy theory. The results of the research show there are undeveloped tourism potencies such as Pondok Klasik and Taman Gumi Banten. Several problems are also faced in the development such as the location of tourist objects are in eruption prone-areas, inadequate amenities, poor accessibilities, unavailable ancillary service including insufficient management of tourist objects, the decreasing number of visitor due to Covid-19 pandemic, and unavailable integrated tourist package which includes the tourist objects in this area. Keywords: volcano, tourism potencies, eruption, eruption prone-areas, tourism development strategy.